Success Factors in the FIFA 2018 World Cup in Russia and FIFA 2014 World Cup in Brazil - Lepschy, Hannes; Woll, Alexander; Wäsche, Hagen (Frontiers in Psychology, 2021)
Research on success factors in football focusing on national teams is sparse. The current study examines the success factors during the World Cup 2018 in Russia and the World Cup 2014 in Brazil. A total of 128 matches were analyzed using a generalized order logit approach. 29 variables were identified from previous research. The results showed that defensive errors (p=0.0220), goal efficiency (p=0.0000), duel success (p=0.0000), tackles success (p=0.0100), shots from counter attacks (p=0.0460), clearances (p=0.0130), and crosses (p=0.0160) have a significant influence on winning a match during those tournaments. Ball possession, distance and market value of the teams had no influence on success. Overall, most of the critical success factors and those with the highest impact on winning close games were defensive actions. Moreover, the results suggest that direct play and pressing were more effective than ball possession play. The study contributes to a better understanding of success factors and can help to improve effectiveness of training, match preparation and coaching.